Studi Histopatologi Organ Insang pada Ikan Nila (Oreochromis niloticus) - Tri Suwarno Handoko Noviyanto; Angela Mariana Lusiastuti; Baiq Hana Susanti (Department of Biology Education, FSTT, Mandalika University of Education, Indonesia., 2022)
This study aims to determine the abnormal tissue structure of the gill organs in Tilapia (Oreochromis niloticus) due to infection. The type of research used is experimental using a randomized design. The research sample used was tilapia infected with the disease, taken from a nursery pond with poor water quality. This can be seen from the macroscopic characteristics of the sick tilapia. This research was conducted at the Histopathology and Pathology Laboratory of the Sempur Freshwater Aquaculture Research Institute, Bogor. Research procedure by making tissue preparations or histological preparations for gill organs. Data analysis by observing and identifying, both macroscopically and microscopically. The results of data processing are presented in the form of a comparison of abnormal tissue images with normal tissue, after going through observation and identification activities. Based on the research that has been done, histopathological studies conducted on the gill organs of Tilapia, indicated that the fish had been infected with the disease. This can be seen from the brownish color of the gills, slow movement, and difficulty breathing. Infection can be caused by pathogens or the influence of the cloudy water quality of the Tilapia fish's habitat.